Career Development of Indonesian National Police: The Case Study Analysis of Police Grand Comissioner Rank - Mustafa Hari Kuncoro; Billy Tunas; Wibowo (Journal of Business and Behavioural Entrepreneurship, 2019)
It was important for Indonesian National Police organizations to be able to managed their human resources through good management by giving employees or members the opportunity to advance. Human resources in one organization had an important role of Indonesian National Police experiences a surplus of members with the position of Police Grand Commissioner. As of the beginning of 2019, this institution had around 1,400 members serving as middle officers. Most of these officers did not get outside structural positions. The development system of the right police career pattern was able to provide direction for individual police officers to developed themselves. The purposed of this research was to analyzed case studies related to the career development of the Police Grand Commissioner ranked that took place at the Institution of Indonesian National Police. This research used a qualitative approach with a case study method. This study concluded that career development was an police's efforts to achieve a career plan. In this case, there were organizational efforts in the form of programs and activities to assisted the career development of Police Grand Commissioner personnel. Another important thing was related to education and training provided to Police Grand Commissioner personnel must be in accordance with the requirements needed, so that the quality improvement of Police Grand Commissioner personnel would be truly fulfilled and aimed to developing police competencies and careers in accordanced with the needs and challenges of Grand Commissioner Police personnel performance.